The Benefits of Adding Corn Stalk Ash as a Substitution of Some Cement Against of Compressive Strength Concrete - Sri Hartati Dewi; Roza Mildawati; Tio Perdana (UIR PRESS, 2019)
Concrete is a very important building material used in the world of construction services, and it is generally known that the good and bad properties of concrete can be seen from its compressive strength. Concrete consists of Portland Cement (PC) or other hydraulic cement, fine aggregates, coarse aggregates, and water, with or without using additional materials. Cement is one of the main mixtures of concrete constituents composed of natural resources such as lime (CaO), Silica (SiO₃), alumina (Al2O₃), little magnesia (MgO), and alkali. Silica is also found in corn. according to (Roesmarkam and Yuwono, 2002) corn plants have a Silica content of 20.6%. This study aims to determine the effect of utilization of corn stalk ash on compressive strength and modulus of elasticity of concrete. Cornstalk ash is used as a partial substitute for cement, with a mixture composition of 2%, 4%, 6%, 8%, and 10%. This study uses SNI 03-2834-2000 for mix design, with the added ingredient of 0.25% sikament NN. Cylindrical test specimen size (150 mm x 300 mm), the specimen was treated and tested at 28 days. Based on research using corn stalk ash 2%, 4%, 6%, 8%, and 10%. either without or using sikament NN the highest compressive strength at 8% is 20.8 Mpa and 20.4 Mpa, and decrease in usage of 10% corn stalk ash which is 18.2 Mpa and 18, 4 Mpa. The highest elastic modulus without or with sikament NN present in 8% ie 21656.14 Mpa and 21607.52 MPa. Modulus of Elasticity value decreased in the use of corn stalks 10% ash is 20366.28 Mpa and 20569.59 MPa. Based on the research, corn stalk ash can replace the role of part of cement in construction using corn stalk ash 8%.